Geospatial analysis with SQL : a hands-on guide to perform geospatial analysis by unlocking the syntax of spatial SQL /: a hands-on guide to perform geospatial analysis by unlocking the syntax of spatial SQL. (2023) - McClain, Bonny P
No abstract available